1998
DOI: 10.1080/10408449891344191
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Endocrine Modulators and Human Health: An Assessment of the Biological Evidence

Abstract: Recently, a great deal of attention and interest has been directed toward the hypothesis that exposure, particularly in utero exposure, to certain environmental chemicals might be capable of causing a spectrum of adverse effects as a result of endocrine modulation. In particular, the hypothesis has focused on the idea that certain organochlorine and other compounds acting as weak estrogens have the capability, either alone or in combination, to produce a variety of adverse effects, including breast, testicular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
102
0
3

Year Published

1999
1999
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 217 publications
(108 citation statements)
references
References 334 publications
3
102
0
3
Order By: Relevance
“…8 As recently suggested by our group, 9 the increased plasma OC concentrations of reduced-obese individuals raise concern about a potentially harmful side effect of weight loss since several pollutants can act as hormone disrupters. 2,5 The clinical significance of the weight lossinduced plasma pollutants levels observed in the present study is, however, as yet unknown. On the one hand, the effect could be negligible since reduced-obese subjects of the present study show several times less body burden than that reported in Inuit adults, 21 a population that does not present any greater level of metabolic disease than the Southern Québec population.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…8 As recently suggested by our group, 9 the increased plasma OC concentrations of reduced-obese individuals raise concern about a potentially harmful side effect of weight loss since several pollutants can act as hormone disrupters. 2,5 The clinical significance of the weight lossinduced plasma pollutants levels observed in the present study is, however, as yet unknown. On the one hand, the effect could be negligible since reduced-obese subjects of the present study show several times less body burden than that reported in Inuit adults, 21 a population that does not present any greater level of metabolic disease than the Southern Québec population.…”
Section: Discussionmentioning
confidence: 63%
“…Consequently, although the use of these substances has been banned or restricted in Western countries, they are still found in virtually every person on the planet and might cause adverse effects in humans. 2,5 Since pollutants are stored in fat, it has been postulated that adipose tissue loss could result in increased organ and blood concentrations of these compounds. 6 A previous study has confirmed this hypothesis by reporting increased dichlorodiphenyl trichloroethane (DDT)-related compounds concentrations in blood, adipose tissue, heart, lung, spleen and brain in starved mice which were a priori treated with a load of 14 C-DDT.…”
Section: Introductionmentioning
confidence: 99%
“…The exposure to these compounds can adversely affect some physiological functions. It was observed that they are able to cause hyperestrogenic effects including uterine enlargement in immature animals, estrus cycle abnormalities and fertility problems [4]. Phytoestrogens were also found to participate in other events, e.g.…”
mentioning
confidence: 96%
“…And they are suspected of being responsible for an increase in the disruption of the normal physiological functions of the endocrine systems of mammals, fish, birds, reptiles and invertebrates (Golden et al, 1998;Tyler et al, 1998). These chemicals include: natural estrogens, such as 17β-estradiol and estrone; synthetic estrogens, such as 17α-ethinylestradiol; as well as xeno-estrogens, such as alkylphenols (including nonylphenol and octylphenol) and Bisphenol A (Gray and Metcalfe, 1997;Staples et al, 1998;Hasselberg et al, 2004;Balch and Metcalfe, 2006).…”
Section: Introductionmentioning
confidence: 99%